kLa based scale-up cultivation of the extremophilic archaeon Sulfolobus acidocaldarius: from benchtop to pilot scale - Rastädter, Kerstin; Wurm, David J.; Spadiut, Oliver; Quehenberger, Julian (Frontiers in Bioengineering and Biotechnology, 2023)
The two major scale-up criteria in continuously stirred bioreactors are 1) constant aerated power input per volume (Pg/VL), and 2) the volumetric O2 mass transfer coefficient (kLa). However, Pg/VL is only influenced by the stirrer geometry, stirrer speed, aeration and working volume, while the kLa is additionally affected by physiochemical properties of the medium (temperature, pH, salt content, etc.), sparging of gas and also by the bioreactor design. The extremophilic archaeon Sulfolobus acidocaldarius, thriving at 75 °C and pH 3.0, has the potential for many biotechnological applications. However, previous studies imply that the family Sulfolobaceae might be affected by higher oxygen concentration in the headspace (>26%). Hence, adequate oxygen supply without being toxic has to be ensured throughout the different scales. In this study, the scale-up criteria Pg/VL and kLa were analyzed and compared in a 2 L chemostat cultivation of S. acidocaldarius on a defined growth medium at 75 °C and a pH value of 3.0, using two different types of spargers at the same aerated power input. The scale-up criterion kLa, ensuring a high specific growth rate as well as viability, was then used for scaleup to 20 L and 200 L. By maintaining a constant kLa comparable dry cell weight, specific growth rate, specific substrate uptake rates and viability were observed between all investigated scales. This procedure harbors the potential for further scale-up to industrial size bioreactors.